First record and a new species of Cylindroxystus Bierig (Coleoptera, Staphylinidae, Paederinae) in Colombia - Ramírez, José; Asenjo, Angélico (Zootaxa, 2017)
Cylindroxystus janualis sp. nov., of the Paederinae, subtribe Cylindroxystina, from Chocó, northwest Colombia is described, illustrated and distinguished from the other species mainly using aedeagal characters. This is the first record of Cylindroxystus Bierig 1943 from Colombia.